1996
DOI: 10.1007/bf00419462
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in microbial mining

Abstract: Microbial mining of copper sulphide ores, has been practiced on an industrial scale since the late 1950s. Since then, advances in microbial mining and the role of microorganisms involved in solubilization of metals have assumed commerical importance. The fact that bioleaching processes save energy, have a minimum pollution potential and are able to yield value-added by-products make these processes invaluable. The metal extraction processes using microorganisms, which are currently in active use, concern coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…Efficient recovery of metals (75%-80% after 48 h of incubation) was achieved during anaerobic leaching at pH 5-6.5 with glucose as the source of organic carbon and temperatures in a range of 30-45 °C. While not directly comparable with other studies, the leach duration was considerably shorter than those reported for fungal production of organic acids [32,357] or the use of RISC-oxidising autotrophs [335].…”
Section: Reductive Bioleaching (Organic Carbon Compound As Electron Dcontrasting
confidence: 75%
“…Efficient recovery of metals (75%-80% after 48 h of incubation) was achieved during anaerobic leaching at pH 5-6.5 with glucose as the source of organic carbon and temperatures in a range of 30-45 °C. While not directly comparable with other studies, the leach duration was considerably shorter than those reported for fungal production of organic acids [32,357] or the use of RISC-oxidising autotrophs [335].…”
Section: Reductive Bioleaching (Organic Carbon Compound As Electron Dcontrasting
confidence: 75%
“…In addition, bioleaching is readily adaptable to low grade ores and does not require a complex plant, such that several countries have already adopted bacterial leaching as a new extractive metallurgical process (Agate 1996;Bosecker 1997;Munoz et al 1995c;Rawlings 1998). However, uranium bioleaching plants have not been opened for a couple of decades.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to the chemical leaching process, the bioleaching process, which employs microorganisms such as bacteria and fungi as the leaching catalysts, is known to be economical and environmentally acceptable (Agate 1996;Bosecker 1997;Munoz et al 1995c). In addition, bioleaching is readily adaptable to low grade ores and does not require a complex plant, such that several countries have already adopted bacterial leaching as a new extractive metallurgical process (Agate 1996;Bosecker 1997;Munoz et al 1995c;Rawlings 1998).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations